The children's Bach - Garner, Helen, 1942- (Pantheon Books, 2023)
"Helen Garner has been a literary institution in Australia for decades. Her perfectly formed novels embodied Australia's tumultuous 70s and 80s, and her incisive nonfiction evokes the keen eye of the New Journalists. The Atlantic dubbed her "the Joan Didion of Australia." Now, The Children's Bach, the beloved work that solidified her place among the masters of modern international letters, is available in a new US edition. The Children's Bach follows Dexter and Athena Fox, a husband and wife who live with their two sons in the inner suburbs of early-1980s Melbourne. Dexter is gregarious, opinionated, and old fashioned. Athena is a dutiful wife and mother, stoic yet underestimated. Though their son's disability strains the family at times, they appear to lead otherwise happy lives. But when a friend from Dexter's past resurfaces, she and her cast of beguiling companions reveal another world to Dexter and Athena: a bohemian underground, unbound by routine and driven by desire, where choice seems to exist independent of consequence. And as Athena delves deeper into this other kind of life, the tenuous bonds that hold the Fox family together begin to fray. Painted on a small canvas and with a subtle musical backdrop, The Children's Bach is "a jewel" among Garner's revered catalog (Ben Lerner), a finely etched masterpiece that weighs the burdens of commitment against the costs of liberation"--